Comparison of Anthropometric Indicators That Assess Nutritional Status From Infancy to Old Age and Proposal of Percentiles for a Regional Sample of Chile - Gómez-Campos, Rossana; Vidal-Espinoza, Rubén; Marques de Moraes, Anderson; Lázari, Evandro; Andruske, Cynthia Lee; Castelli Correia de Campos, Luis; Urzua-Alul, Luis; Cossio-Bolaños, Wilbert; Cossio-Bolanõs, Marco A. (Frontiers in Nutrition, 2021)
Objectives: Anthropometric variables are used to evaluate health, dietary status, disease risks, and changes in body composition. The purpose of this study was to compare weight, height, and Body Mass Index (BMI) with American references from the National Center for Health Statistics (NCHS-2012), using BMI and the Tri-Ponderal Index (TMI) to propose percentiles for evaluating nutritional status of children, adolescents, and adults, ages 5 to 80 years old. Methods: Weight and height of 15,436 individuals (8,070 males and 7,366 females) were evaluated. BMI and TMI were calculated. Results: The results illustrated that children were heavier and had more BMI during childhood compared to the NCHS references. During adolescence, reference values were greater until approximately ages 70-79. For height, children were relatively similar to those of the NCHS references, but during adolescence, differences became evident. Adolescence until approximately age 80, the population showed lower values for height. Percentiles were calculated using BMI and TMI by age range and sex. Differences occurred between the American NCHS references and the population with regard to the anthropometric variables of weight, height, and in BMI. Conclusions: Percentile references were developed for BMI and TMI to evaluate the nutritional state. We suggest using these results in clinical and epidemiological contexts.